Comparison of Shod and Unshod Gait in Patients With Parkinson's Disease With Subthalamic and Nigral Stimulation - Horn, Martin A.; Gulberti, Alessandro; Hidding, Ute; Gerloff, Christian; Hamel, Wolfgang; Moll, Christian K. E.; Pötter-Nerger, Monika (Frontiers in Human Neuroscience, 2022)
Background: The Parkinsonian (PD) gait disorder represents a therapeutical challenge with residual symptoms despite the use of deep brain stimulation of the subthalamic nucleus (STN DBS), medical and rehabilitative strategies. The aim of this study was to assess the effect of different DBS modes as combined stimulation of the subthalamic nucleus and substantia nigra (STN+SN DBS) and environmental rehabilitative factors as footwear on gait kinematics. Methods: This single-centre, randomized, double-blind, cross-over clinical trial assessed shod and unshod gait in PD patients with medication in different DBS conditions (STIM OFF, STN DBS, STN+SN DBS) during different gait tasks (normal gait, fast gait, gait during dual task) and compared gait characteristics to healthy controls. 15 patients participated in the study, 11 patients were analysed after a dropout of 4 patients due to DBS-induced side effects. Results: Gait was modulated by both factors, footwear and DBS mode, in PD patients. Footwear impacted gait characteristics in PD patients similarly to controls with longer step length, lower cadence and shorter single-support time. Interestingly, DBS exerted specific effects depending on gait tasks with increased cognitive load. STN+SN DBS was the most efficient DBS mode compared to STIM OFF and STN DBS with intense effects as step length increment during dual task. Conclusions: The PD gait disorder is a multifactorial symptom, impacted by environmental factors as footwear and modulated by DBS. DBS effects on gait were specific depending on the gait task, with the most obvious effects with STN+SN DBS during gait with increased cognitive load.